A Narrative Literature Review of the 2011 Joplin, Missouri Tornado: Myriad Lessons Learned from One of the Worst Tornadoes in U.S. History - Stimers, Mitchel; Paul, Bimal Kanti (Prevention and Treatment of Natural Disasters, 2025)
We examined the impacts and lessons learned from the 2011 Joplin, Missouri, tornado, one of the most devastating tornadoes in U.S. history. The review covers various aspects, including vulnerability and resilience, building codes, preparedness, risk communication, damage assessment, economic impacts, and response and recovery strategies. Key findings highlight the role of building codes and structural integrity in mitigating damage, the importance of effective communication and preparedness in enhancing community response, and the significant influence of socioeconomic factors on recovery processes. Studies on community resilience emphasize the necessity of integrated approaches that combine engineering, social, and economic perspectives. The review also underscores the value of empirical data from building permit records, spatial‑temporal analyses, and economic models in understanding recovery trajectories. Contributions from interdisciplinary research provide insights into improving disaster preparedness, response strategies, and long‑term resilience. The analysis offers valuable lessons for policymakers, emergency management officials, and urban planners, aiming to enhance resilience and reduce vulnerability to future tornadoes and other natural disasters. The review’s findings suggest that proactive planning, robust building practices, and effective communication are crucial for fostering resilient communities capable of withstanding and recovering from severe weather events.